﻿A new species of the genus Separatatus Chen & Wu (Hymenoptera, Braconidae, Alysiinae) from South Korea - Ju-Hyoeng Sohn; Cornelis van Achterberg; Sangjin Kim; Jongok Lim; Hyojoong Kim (ZooKeys, 2022)
Separatatus megagnathus sp. nov. is recorded as new to science from South Korea. Due to this record, the genus Separatatus Chen & Wu, 1994 (Braconidae: Alysiinae) is recognized for the first time from South Korea. The genus and species are described and illustrated herein plus an identification key including the Korean new species is provided. In addition, the DNA barcode region of the mitochondrial cytochrome c oxidase subunit I (COI) has been analyzed for the new species.